The Concept of Islamic Moderation: A Response to the Polemics of Interfaith Marriage in Indonesia - Rahmah, Putri Jannatur (Universitas Muhammadiyah Metro, 2024)
The phenomenon of interfaith marriages continues to be an issue of controversy. While this type of marriage offers a huge opportunity for strengthening interfaith relations, the obstacles they're faced with are extremely critical. People in interfaith marriages must always deal with worries about societal involvement and adaptability, not simply on an individual stage but also within their wider families, the country itself, and their future kids. Considering these problems, living in a fast-globalizing civilization where individuals from different cultures are frequently interacting indicates that marriages between people of different faiths will continue to be common. As a result, the purpose set by the writer in this research is to examine the issue of marriage between faiths in Indonesia from the perspective of Islamic moderation. Given the fact that Indonesia has the world's biggest Muslim population, religious beliefs and social behaviors will always be rooted in society's traditions. The methodology applied to this study is qualitative research utilizing library-based collecting techniques; the writer gathers data from publications, scientific journals, and other resources. The author utilizes qualitative research, which provides data presented in the form of observations and descriptions integrated within the text under analysis. Moderation in Islam, as a concept, presents a holistic perspective. A decision must take into account a variety of variables, which involve not only religious beliefs but also mental, moral, social, and other considerations. Islamic moderation is a useful instrument for addressing the phenomenon of interfaith marriage that has emerged in Indonesia. Moderation is a heart; moderation is a way